2015
DOI: 10.1016/j.nucengdes.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of supercritical carbon dioxide flow in see-through labyrinth seals

Abstract: This paper presents a numerical study of Supercritical Carbon Dioxide (sCO 2) flow in see-through labyrinth seals. The Computational Fluid Dynamic (CFD) simulation of this scenario is performed under the framework of OpenFOAM. Properties of sCO 2 are implemented into OpenFOAM with a user-defined interface. A test facility was constructed to measure the leakage rate and pressure drop of sCO 2 in see-through labyrinth seals. Various designs and conditions have been tested to study the flow characteristic and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…They concluded that the pressure drop of PCHE with S-shaped fins is 4-5 times lower than that of PCHE with zig-zag channels but at the same time Nusselt number is 24-34% lower depending on the Reynolds number. Ngo et al [15] extended the range of operating parameters for both the PCHEs tested by Nikitin et al [14] to study the influence of Prandtl number variation on their thermal-hydraulic performance. They used integral form of log-mean temperature difference (LMTD) to calculate the overall heat transfer coefficients since the operating conditions are closer to the critical point where specific heat varies drastically with the temperature.…”
Section: Pche Testing and Modeling Work At Tokyo Institute Of Technologymentioning
confidence: 99%
“…They concluded that the pressure drop of PCHE with S-shaped fins is 4-5 times lower than that of PCHE with zig-zag channels but at the same time Nusselt number is 24-34% lower depending on the Reynolds number. Ngo et al [15] extended the range of operating parameters for both the PCHEs tested by Nikitin et al [14] to study the influence of Prandtl number variation on their thermal-hydraulic performance. They used integral form of log-mean temperature difference (LMTD) to calculate the overall heat transfer coefficients since the operating conditions are closer to the critical point where specific heat varies drastically with the temperature.…”
Section: Pche Testing and Modeling Work At Tokyo Institute Of Technologymentioning
confidence: 99%
“…The results of the experimental research and the CFD calculations of the flow in a straight-through labyrinth seal are included in Yuan et al (2015). The CFD calculations were carried out within the framework of OpenFOAM.…”
Section: Introductionmentioning
confidence: 99%
“…Pugachev et al [21,22] used a CFD model to research the direction of the main vortex in a short chamber with a backward-facing step and numerically and experimentally verified that the segmentation negatively affects the leakage performance and stiffness coefficients of the brush-labyrinth sealing configuration. Yuan et al [23] established a CFD model to optimize the seal design for supercritical carbon dioxide in turbomachinery, and the model was then confirmed based on the experimental results.…”
Section: Introductionmentioning
confidence: 99%